Analysis of International Service Standards of International Patient Management - E. V. Chernyshev; G. D. Petrova (Здоровье мегаполиса)
Background. The article is the first to analyze international certification systems for medical tourism as key drivers for growing export of medical services while healthcare is getting international and Russian medical advances are introduced to the global market. Results. The macro-regional activity of international certification systems and their scope of application—from the quality and safety of medical care to service standards of communication with foreign citizens—are analyzed. The Patients International certification standards were examined in detail. It was evaluated to what extent various departments of a healthcare organization are involved in the implementation of international standards.